Analysis of the Difficulties in Learning Indonesian for Foreign Students in Batam - Maya Marsevani; Widia Yanelyn; Dinti Fahlianti; Pawinee Suksawai; Nantakarn Tohmi; Pebiana Pebiana; Jacson Jacson (Universitas Negeri Makassar, 2023)
Abstract. Learning Indonesian language is one of subjects that has to be understood by foreign students in Batam. However, the learning process sometimes could not run well because of foreign studentsâ€™ ability in learning Indonesian language was still low. Hence, this research aims at analyzing the learning difficulties of foreign students in learning Indonesian language.This research employs mixed methods. Furthermore, this research conducted in one of private schools in Batam with a total of 25 foreign students. The authors distributed questionnaires and conducted interviews to obtain the data. The results shows that there were several difficulties faced by the foreign students in learning Indonesian language such as difficulties in learning speaking, reading, writing, and listening skills and pronouncing Indonesian words. It can be concluded that these difficulties arose due to differences in cultural and language background, lack of time to learn and practice, as well as BIPA materials which they found very challenging. The authors hope that the teachers can improve their motivation in learning Indonesian language by providing interesting learning materials.Â Keywords: Indonesian Language, Foreign speakers, Learning Program, Learning Difficulties